Early enzyme replacement therapy prevents dental and craniofacial abnormalities in a mouse model of mucopolysaccharidosis type VI - Nagpal, Rohit; Georgi, Gina; Knauth, Sarah; Schmid-Herrmann, Carmen; Muschol, Nicole; Braulke, Thomas; Kahl-Nieke, Bärbel; Amling, Michael; Schinke, Thorsten; Koehne, Till; Petersen, Julian (Frontiers in Physiology, 2022)
Mucopolysaccharidosis VI (MPS VI) is a hereditary lysosomal storage disease caused by the absence of the enzyme arylsulfatase B (ARSB). Craniofacial defects are common in MPS VI patients and manifest as abnormalities of the facial bones, teeth, and temporomandibular joints. Although enzyme replacement therapy (ERT) is the treatment of choice for MPS VI, the effects on the craniofacial and dental structures are still poorly understood. In this study, we used an Arsb-deficient mouse model (Arsbm/m) that mimics MPS VI to investigate the effects of ERT on dental and craniofacial structures and compared these results with clinical and radiological observations from three MPS VI patients. Using micro-computed tomography, we found that the craniofacial phenotype of the Arsbm/m mice was characterized by bone exostoses at the insertion points of the masseter muscles and an overall increased volume of the jaw bone. An early start of ERT (at 4 weeks of age for 20 weeks) resulted in a moderate improvement of these jaw anomalies, while a late start of ERT (at 12 weeks of age for 12 weeks) showed no effect on the craniofacial skeleton. While teeth typically developed in Arsbm/m mice, we observed a pronounced loss of tooth-bearing alveolar bone. This alveolar bone loss, which has not been described before in MPS VI, was also observed in one of the MPS VI patients. Interestingly, only an early start of ERT led to a complete normalization of the alveolar bone in Arsbm/m mice. The temporomandibular joints in Arsbm/m mice were deformed and had a porous articular surface. Histological analysis revealed a loss of physiological cartilage layering, which was also reflected in an altered proteoglycan content in the cartilage of Arsbm/m mice. These abnormalities could only be partially corrected by an early start of ERT. In conclusion, our results show that an early start of ERT in Arsbm/m mice achieves the best therapeutic effects for tooth, bone, and temporomandibular joint development. As the MPS VI mouse model in this study resembles the clinical findings in MPS VI patients, our results suggest enzyme replacement therapy should be started as early as possible.